Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1007/s10163-014-0278-2
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on the characteristics and management of dental waste in Urmia, Iran

Abstract: The objective of this study was to identify the components, composition, generation rate and management of dental waste in Urmia, Iran. Fifteen dental centers including eight general dental offices, five specialist dental offices and two dental clinics were selected and two samples were taken from each office. Then, the wastes were manually separated in 31 components and weighted. The results showed that total dental waste generation in all general dental offices, specialist dental offices and dental clinics w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 21 publications
0
10
0
2
Order By: Relevance
“…Based on its types, personal dental health services generated wool or cotton and infectious gauze contaminated with blood and saliva, toxic wastes as dental acrylic gypsum and radioactive material such amalgam as teeth fillings and unplugged amalgam. Based on Kooviland’s study, the most potential infectious waste products are paper towels (gauze) contaminated with blood (3.88 kg), toxic film waste of x-ray blast (2.75 kg) and the most chemical waste is dental printing materials (3.99 kg) [12].…”
Section: Discussionmentioning
confidence: 99%
“…Based on its types, personal dental health services generated wool or cotton and infectious gauze contaminated with blood and saliva, toxic wastes as dental acrylic gypsum and radioactive material such amalgam as teeth fillings and unplugged amalgam. Based on Kooviland’s study, the most potential infectious waste products are paper towels (gauze) contaminated with blood (3.88 kg), toxic film waste of x-ray blast (2.75 kg) and the most chemical waste is dental printing materials (3.99 kg) [12].…”
Section: Discussionmentioning
confidence: 99%
“…Waste prevention or minimization should be focused as the priority principle in waste management system (Kim and Long, 2011;López-Delgado and Tayibi, 2012). Manufacturers should reduce generation of hazardous substances and increase use of recycled materials (Koolivand et al, 2014). If a source separation system is to be implemented, containers of different sizes and shapes (one for each category of waste) can be placed at suitable locations.…”
Section: 2 Managementmentioning
confidence: 99%
“…An investigation carried out on the characteristics and management of dental wastes in Urmia, Iran, showed that 31 components were manually separated and weighted. The results showed that domestic, potentially infectious, toxic, chemical and pharmaceutical wastes were 35.46%, 34.24%, 11.83% and 5.56%, respectively (32). In dental centers in Esfahan city, the amount of infectious, non-infectious and domestic wastes were obtained as 45.07%, 12.15% and 42.78%, respectively (33).…”
Section: Discussionmentioning
confidence: 94%